THEOLOGICAL AND EDUCATIONAL IMPLICATIONS OF THE VIRTUE OF THE KNOWLEDGEABLE: A TEXTUAL ANALYSIS OF HADITH ABU DAUD 3157 - Sera Yuliantini (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2026)
This study examines the hadith regarding the virtues of the learned, narrated by Imam Abu Daud, no. 3157, in Maktabah Baitul Afkar Ad-Dauliah. The study aims to understand the essence of the virtues of the learned from an Islamic perspective and to analyze the quality of the hadith’s isnad and matn. The study employs a qualitative approach using a literature review methodology. Primary data sources consist of hadith collections and literature related to knowledge and the virtues of scholars, while secondary data sources were obtained from books, journals, and other scholarly references. Data collection techniques involved documentation and observation of various literary sources. Data analysis techniques included data reduction, data presentation, as well as verification and drawing conclusions. The research findings indicate that knowledge holds a very important position in Islam as it serves as a means to attain salvation, happiness, and the nobility of life in this world and the hereafter. Those who possess knowledge attain a high status in the sight of Allah SWT, as explained in Surah Al-Mujadalah, verse 11, which states that Allah will elevate the status of those who believe and possess knowledge. A hadith narrated by Imam Abu Daud, number 3157, explains that seekers of knowledge will have their path to Paradise made easier; the angels will be pleased with them and pray for them; all creatures in the heavens and on earth will ask for forgiveness for them; and scholars are the heirs of the prophets. Based on an analysis of the chain of transmission (sanad), this hadith has a continuous (muttasil) chain, and the majority of its narrators are deemed trustworthy (tsiqah) by hadith scholars. Meanwhile, an analysis of the text (matan) indicates that the content of the hadith does not contradict the Qur’an, other authentic hadiths, sound reason, or historical facts; thus, no elements of oddity (syadz) or flaws (illat) are found. This hadith is also supported by other narrations from Imam Tirmidhi, Ibn Majah, Imam Ahmad bin Hanbal, and Imam Darimi, which have different wording but convey the same meaning. Thus, the hadith narrated by Imam Abu Daud, number 3157, can be declared authentic in terms of both its chain of transmission and its text, and serves as an important foundation regarding the virtue of seeking and applying knowledge in life.